Working on mental health stigma in education: a multicentre community-based clinical trial - Lucía Santonja-Ayuso; Laura Andreu-Pejó; José Vicente Carmona-Simarro (Frontiers in Public Health, 2025)
BackgroundHigh school teachers have a key role to play in supporting their students in this stage of adolescent growth, especially given the increasing prevalence of mental disorders in this population. However, it has been observed that these teachers lack confidence, commitment and knowledge related to the management of mental health problems and show a high level of stigma. The goal of this research was therefore to evaluate the effectiveness of a mental health prevention and promotion training programme by led mental health nurse, aimed at reducing the stigmatising attitudes of teachers at schools in Spain.MethodsA multicentre, non-randomised, community-based study was therefore carried out, with a pre-post-test and a three-month follow-up. The teachers (n = 169) were divided into the experimental group (n = 103) and the control group (n = 66). The training programme was conducted over different 4 different sessions (8 h in total) and the dependent variable was the Stigma Attribution Scale.ResultsStatistical analyses showed a significant improvement in the level of stigma at the post-programme evaluation for all scale dimensions except Responsibility and Help, which were also maintained over time, since at 3 months the reduction in the level of teacher stigma was lower for all scale dimensions except Responsibility and Avoidance. The effect size of the improvement in stigma level was moderate-high for Pity, Coercion and Segregation (d ≥ 0.5).ConclusionThis training programme based on anti-stigma measures led by a mental health nurse was effective in reducing stigmatising attitudes in high school teachers in both the short and the long term.Clinical trial registrationhttps://doi.org/10.1186/ISRCTN63945853, identifier ISRCTN63945853.